Relationship of Sleep Quality to Academic Achievements of Students Faculty of Medicine Tarumanagara University - Barii Ikraam; Djung Lilya Wati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Medical students have a heavy academic burden that impacts poor sleep quality. Sleep has a close relationship with cognition, so it is associated with various types of memory, such as long-term and working memory, as well as some material, declarative, procedural/non-declarative knowledge, and several stages of memorization such as consolidation, coding, and reconsolidation. This study aims to determine the relationship between sleep quality and students' academic achievement at the Faculty of Medicine, Tarumanagara University. This study used a research design in the form of observational and cross-sectional as a research study design. Sampling using simple random sampling and obtained as many as 152 students of the Faculty of Medicine, University of Tarumanagara became respondents in this study. The Pittsburgh Sleep Quality Index (PSQI) questionnaire assesses sleep quality. Academic achievement is assessed on the value of blocks completed. The statistical test in this study used Chi-square to see the relationship between sleep quality and academic achievement. It was found that 126 respondents (82.9%) had poor sleep quality. Test Chi-square shows no relationship between Gender, age, class, napping habits, sleeping with other people, eating before bed, using gadgets before bed, using gadgets without blue light filters, and using gadgets for 24 hours on sleep quality. (p> 0.05). Furthermore, there is no relationship between sleep quality and academic achievement (p> 0.05) among students of the Faculty of Medicine, Tarumanagara University. In conclusion, this study's results indicate no relationship between sleep quality and academic achievement of students at the Faculty of Medicine, Tarumanagara University.